Legal Responsibility for Type C Mining Activities : a Study in Gondang District, Mojokerto, Indonesia - Mustiko Romadhoni Putro Widodo; Dudik Djaja Sidarta; Subekti Subekti (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2024)
mining activities are an important sector in the extractive industry which has the potential to make a significant economic contribution. However, in Gondang sub-district, Mojokerto Regency, East Java, C excavation mining activities also face challenges in terms of legal accountability. This research aims to analyze legal aspects related to the accountability of C excavation mining business actors in the area. The research methods used are literature studies and interviews with related parties, such as local government, business actors and the community. The research results show that there are a number of legal problems related to licensing, implementation of activities, and environmental impacts. Business actors often ignore legal obligations related to business permits, environmental protection and corporate social responsibility. The monitoring and law enforcement system at the local level also still experiences obstacles which result in a lack of effective sanctions for violations. Recommendations from this research include increasing coordination between relevant parties, implementing stricter environmental audits, and stricter law enforcement to ensure compliance with applicable regulations. With these steps, it is hoped that excavation C mining activities in Gondang District can take place sustainably and provide optimal benefits without harming the environment and society.